Implants in Orthopaedic Dentistry (International Journal of Scientific Trends, 2024)
With the help of implantation, it is possible to restore a beautiful smile if one or more teeth are lost. The procedure is the implantation of a screw or implant into the lower or upper jaw, which will act as an artificial root. Let's take a closer look at what they are and how they differ.